2017
DOI: 10.1093/cid/cix095
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Function Failure Is Associated With Human Immunodeficiency Virus Disease Progression

Abstract: This work establishes the relevance of thymic function, measured by sj/β-TREC ratio, in HIV disease progression by analyzing a large number of patients in 3 cohorts with different HIV disease progression phenotypes. These results support and help to understand the mechanisms underlying the rationale of early cART onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 33 publications
3
26
0
2
Order By: Relevance
“…showed that INRs had a lower naïve CD4 + T‐cell increase and a lower percentage of CD4 + RTE than immunological responders and healthy controls, indicating that reduced thymic output may be a major mechanism of incomplete immune reconstitution . In accordance, it has been reported that thymic function, measured by the sj/β‐TREC ratio or CD4 + RTE%, can predict HIV‐1 disease progression in HIV‐1‐infected adults and adolescents with perinatally acquired HIV‐1 . These studies indicate that reduced thymic output may play an important role in the incomplete immune reconstitution of HIV‐1‐infected individuals.…”
Section: Potential Mechanisms Of Incomplete Immune Reconstitutionsupporting
confidence: 63%
See 1 more Smart Citation
“…showed that INRs had a lower naïve CD4 + T‐cell increase and a lower percentage of CD4 + RTE than immunological responders and healthy controls, indicating that reduced thymic output may be a major mechanism of incomplete immune reconstitution . In accordance, it has been reported that thymic function, measured by the sj/β‐TREC ratio or CD4 + RTE%, can predict HIV‐1 disease progression in HIV‐1‐infected adults and adolescents with perinatally acquired HIV‐1 . These studies indicate that reduced thymic output may play an important role in the incomplete immune reconstitution of HIV‐1‐infected individuals.…”
Section: Potential Mechanisms Of Incomplete Immune Reconstitutionsupporting
confidence: 63%
“…50 In accordance, it has been reported that thymic function, measured by the sj/ -TREC ratio or CD4 + RTE%, can predict HIV-1 disease progression in HIV-1-infected adults and adolescents with perinatally acquired HIV-1. 51,52 These studies indicate that reduced thymic output may play an important role in the incomplete immune reconstitution of HIV-1infected individuals. Conversely, Cobos Jiménez et al found in HIV-1infected ART-experienced 45-year-old adults with detectable viremia (<50 copies/ml) for at least 1 year, the percentage of CD31 + CD4 + cells and Sj-TREC content in PBMCs are much higher than those in healthy controls.…”
Section: Thymus and Naïve Cellsmentioning
confidence: 95%
“…Among the multiple factors correlated with poor CD4 cell recovery, defective thymic output has been recognized as one of the most important factors (Ferrando-Martinez et al, 2017;Li et al, 2011;Zakhour et al, 2016). Two strategies have been considered to translate this observation into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…As the thymus decreases in size with age, its relative contribution to the peripheral T cell pool remains poorly understood. Several studies support a significant role for the thymus in T cell regeneration, even during aging, most evidently during certain T cell-lymphopenic conditions (Douek et al 1998, Ferrando-Martinez et al 2017.…”
Section: The Effect Of Pregnancy On the Thymusmentioning
confidence: 95%